Catalogue of living crinoids (Echinodermata: Crinoidea) from Brazil - Gondim, Anne Isabelley; de Moura, Rafael Bendayan; Christoffersen, Martin Lindsey (Zootaxa, 2021)
Knowledge of living crinoids from Brazil is chiefly restricted to the contributions of Dr Luis Roberto Tommasi between the decades of 1950 and 1970. Herein we present an updated catalogue of the crinoids occurring along the Brazilian coast, including data on synonyms, type localities, type material, geographical distribution, bathymetric ranges, and occurrences of species along the coast. The data is based on an extensive revision of the literature and on a survey of several databases. A total of 20 species were catalogued, of which two are endemic (Phrixometra longipinna var. brasiliensis and Thaumatometra minutissima). According to information from the literature, P. longipinna var. brasiliensis represents an undescribed taxon. Although Brazil supports the greatest number of crinoid species in the Southwestern Atlantic, its crinoid fauna remains understudied and likely underestimated. Research on crinoids remains a subject of great potential, not only for taxonomy but also for other areas of knowledge.